Teaching with Technology: Multiple Perspectives for Diverse Scenarios - Agullo-Giles, Marcela (2022)
Due to their multimodal and ubiquitous nature, digital technologies pose challenges and opportunities in teaching design. Although they generate doubts regarding their operation and the gaps that multiply in the light of the new pandemic scenarios, they emerge as a condition of possibility to create proposals that invite students to become protagonists of their own learning process. Their attributes of malleability and connection with authentic settings position digital technologies as a very powerful resource to promote differentiation and diversity in the classroom. The aim of this article is to analyze the characteristics of digital media and explore the ways in which they can be included in teaching proposals.